Metamaterial inspire multiband monopole antenna with defected ground structure - Madhav, B T P; Thirumalarao, K; Venkateswara Rao, M; Saiteja, V N V; Kranthi Kumar, J; Reavanth, P N V S (International Journal of Engineering and Technology, 2017)
This article represents the design and analysis of a compact antenna of size 34mmX18mmX1.6mm on FR-4 substrate material. The designed antenna is having a slot at the partial ground for all iterations are observed and it is analysed with the help of ANSYS 17 Electronics Desktop. A new unit cell design which exhibits the metamaterial property is also analyzed with the help of unit cell analysis. The negative permittivity value is extracted, and that unit cell is implemented in the proposed antenna. The enhanced results have been carried out with comparing iteration wise. The proposed antenna has radiation efficiency of 94%, it works in the range of for LTE (33-37) band at 1.95-2.04 GHz, WiMAX band 2.87-3.76 GHz and LTE (43-44) bands 5.92-7.2 GHz.